Objectified bodies: an interpretation of Herencia by Clorinda Matto de Turner - Valdano, Clara Verónica (2011)
In this article, Karl Marx’s theory on consumer goods and on the values of use and exchange, as well as the reflections of feminist De Luce Irigaray found in “Women on the Market”, help us analyze social relationships in the XIX Century, and to view Lima as a big market where middle-class society uses objects in fashion to pretend a higher position. In this urban space, which seems to be overwhelmed by object to buy and sell, Margarita and Lucía pose as buyers, not only of objects but also of bodies; in this sense, Margarita is a body displayed in the great showcase that is Lima, where the high class must observe, accept, or reject her. She is of mestizo origin, but what does matter is the looks of her body and what she shows or pretends to possess, which ultimately gives her a husband. The article shows how the feminine body has an exchange value since, when pretending, one can aim for a higher class candidate too; nevertheless, in this novel both feminine and masculine bodies get to have a value of use or exchange that is not measured by what one is but by one pretends to be through fashion and luxury.